Prevalência da discriminação autopercebida nos serviços de saúde e fatores associados em idosos brasileiros - Felin, Carolina Marchesan (2021)
Discrimination is a process resulting from human interaction, capable of having a great impact on the quality of life of individuals. Understanding different experiences of discrimination in the elderly and their possible associations are important steps to determine the best way to deal with individual and social discrimination and the impacts on the health of this population. The objective of this dissertation was to verify the prevalence and factors associated with self-perceived discrimination in Brazilian adults and elderly people aged 50 years or over, as well as to explore gender differences in the factors associated with discrimination reported in health services. Data from the Longitudinal Health Study of Elderly Brazilians (ELSI-BRAZIL), a cross-sectional home-based study, were used, in which a national sample of 9412 non-institutionalized people, representative of the population aged 50 years or older, was selected. In this research, self-perceived discrimination was evaluated when seeking medical services or health care and adjusted models for demographic, socioeconomic, psychosocial and behavioral variables. The analysis of this dissertation explored gender differences in the factors associated with discrimination in health services. Poisson regression was used using the svy command to obtain the crude and adjusted prevalence ratios. About 10.9% (95% CI: 10.1-12.1) of the sample reported discrimination when seeking health care. For the female sex, the reports were associated with yellow (PR 2.2IC95%: 1,1-4,9) or indigenous (PR 1.9IC95%: 1,1-3,4) skin color, being over eighty years of age (PR 0.5IC95%: 0,3-0,9), low confidence in the neighborhood (PR 1.4IC95%: 1,1-1,7), negative diagnosis of depression (PR 0.5IC95%: 0,4-0,6) and high satisfaction with life (PR 0.5IC95%: 0,4-0,7). For males, black men (PR 1.8IC95%: 1,2-2,8) and brown (PR1.3IC95%: 1,1-1,8), as well as those with low social confidence (PR 1.5 IC95%: 1,2-1,9), were associated with discrimination in the demand for health services. Therefore, it was observed that for female individuals, the variables of the sociodemographic and psychosocial blocks showed an association with discrimination in the demand for health services. For males, there was no association of discrimination with age, wealth, education or life satisfaction. Composed of the variables use of health services in the last year and smoking, the behavioral block showed no association with discrimination. It was possible to perceive that the influence of aging for men is different from its influence for women for the self-perception of discrimination, since a negative association was found between discrimination and being 80 years old for females, while for men there was no association significant in any age group.